Entrepreneurship in Imperial Russia and the Soviet Union - Carstensen, Fred V., 1944-; Guroff, Gregory, 1941- (Book collections on Project MUSE., 1983)
This multidisciplinary study of entrepreneurship in Russian society from the sixteenth to the twentieth century demonstrates the crucial influence of central government on economic initiative. Originally published in 1983. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.